2016
DOI: 10.1631/jzus.a1600026
|View full text |Cite
|
Sign up to set email alerts
|

Developing planning indicators for outdoor wind environments of high-rise residential buildings

Abstract: Abstract:The construction of a building may change the microclimate in the vicinity, and planning indicators in a master plan may directly affect the outdoor physical environmental quality in residential areas. An inappropriate plan for a site may accelerate wind and intensify vortexes over places on the pedestrian levels, which leads to an adverse outdoor environment. Therefore, the design of a cluster of buildings should not focus only on the buildings but also provide a good outdoor environment around the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…“PO” is another output index of enterprise technology innovation capability in PC, which is divided into four sub-indexes, including the NDP (Shi et al , 2016), DPL (Furman et al , 2000), construction area of the project ( CAP ) (Ying et al , 2016) and APRC (Zhang et al , 2017). These sub-indexes are not available in conventional construction and other fields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…“PO” is another output index of enterprise technology innovation capability in PC, which is divided into four sub-indexes, including the NDP (Shi et al , 2016), DPL (Furman et al , 2000), construction area of the project ( CAP ) (Ying et al , 2016) and APRC (Zhang et al , 2017). These sub-indexes are not available in conventional construction and other fields.…”
Section: Methodsmentioning
confidence: 99%
“…Construction area of the project. The construction area of PC projects indicates the project's scale (Ying et al, 2016). The number of projects and the CAP has a positive correlation, but reflect different aspects of technology innovation capability of a construction enterprise in PC.…”
Section: Output Of Enterprise Technology Innovation Capability In Pre...mentioning
confidence: 99%
“…As building height has influence on wind distribution [29] , the vertical layout on wind environment is studied.…”
Section: Vertical Layout Influencementioning
confidence: 99%
“…In recent years, there have been some important results for the research on the correlation between pollutant dispersion and wind environment, as shown in Table 1. It includes the research methods of the relationship between pollutant diffusion and wind environment [6][7][8][9][10][11][12], the influence of wind on urban pollution diffusion at various scales [13][14][15][16][17][18][19], the relationship between wind, pollutant diffusion and urban scale layout [20][21][22][23][24][25][26][27][28][29], and the establishment of new ventilation efficiency evaluation index [30]. From these studies, the following conclusions can be drawn:…”
Section: Introductionmentioning
confidence: 99%